Laparoscopically assisted cecal cannulation in standing horses - Carvalho, Brenda Ventura Lopes; de Souza, Maria Carolina Neves; Avanza, Marcel Ferreira Bastos; Teixeira, Raffaella Bertoni Cavalcanti; Silva, José Ricardo Barbosa; da Silva Cardoso, Thiago; Novais, Luis Gustavo e Silva; de Oliveira Monteiro, Francisco Décio; Viana, Rinaldo Batista; Monteiro, Bruno Moura; Teixeira, Pedro Paulo Maia; Filho, José Dantas Ribeiro (Frontiers in Veterinary Science, 2026)
IntroductionAccess to the equine cecum is required for various therapeutic and experimental procedures, including decompression, fluid therapy, and transfaunation. Traditional approaches via laparotomy are highly invasive. This study aimed to describe a minimally invasive, laparoscopically assisted technique for cecal cannulation in standing horses.MethodsSeven horses underwent the procedure under sedation and paravertebral anesthesia. Two right flank accesses were created: a 10-mm laparoscopic port for visualization and a 2-cm minilaparotomy for cecal exteriorization. A Foley catheter was inserted via typhlotomy and secured with seromuscular sutures. Postoperative management included clinical monitoring and two sessions of intracecal fluid therapy.ResultsThe technique was successfully completed in six of seven horses (85.7%). The catheter remained functional and was used for repeated fluid administration over 22 days without leakage. Horses maintained normal appetite, behaviour, and intestinal motility. One horse developed fatal peritonitis following immediate postoperative fluid therapy, highlighting the importance of a 24–48 h recovery period before high-volume infusion. Local wound exudation was managed effectively without systemic complications.DiscussionThis standing laparoscopic technique provides a safe, practical, and minimally invasive method for establishing long-term cecal access. It offers a significant advantage over traditional laparotomy by reducing surgical trauma and enabling repeated postoperative therapeutic interventions for conditions like impaction or dysbiosis.